Isolasi Bakteri Asam Laktat dari Usus Sapi (Bos taurus) serta Kemampuannya dalam Menghambat Pertumbuhan Bakteri Eschericia coli dan Shigella sp - Lulu Fatma Dewi; Sartini Sartini; Rahmiati Rahmiati (Universitas Medan Area, 2019)
The purpose of this research was to determine the ability of BAL from cattle intestine (Bos taurus) in inhibiting the growth of Eschericia coli and Shigella sp. Testing of BAL capability in inhibiting growth of Escherichia coli and Shigella sp. using the disc-diffusion method or the Kirby-Bauer method, which was done by measuring the inhibit zone around the paper disc. Data were analyzed descriptively by displaying data in table and picture form. The results obtained 2 isolates of BAL from the cow intestine. All isolates showed positive results when tested for antibacterial against Escherichia coli and Shigella sp. In isolate BAL with code sp1 has inhibition zone against Escherichia coli equal to 7.5 mm and to Shigella sp. of 6.8 mm, whereas in isolate BAL with code sp2 has inhibition zone against Escherichia coli equal to 8.9 mm and to Shigella sp. of 8.0 mm. Based on the results obtained, it can be concluded that isolates of lactic acid bacteria with sp2 code has inhibition zone 8.9 mm in inhibiting Eschericia coli while against bacteria Shigella sp. has a diameter of 8.0 mm.